Novel miniaturized multiband antenna and applications for smart navigation media. Issue 11 (4th September 2019) - Fady, Brahim; Terhzaz, Jaouad; Tribak, Abdelwahed; Riouch, Fatima; Mediavilla, Angel
Abstract: This article presents a novel low‐cost integrated multiband antenna design customized for navigation media applications. The distinctive feature of the design consists in using a broadband planar dipole with four arms and a miniaturized feeding‐point, easy to deploy inside the tracking devices, and cost‐effective for supply chain industry. The article first introduces the main challenges and the benefits of miniaturizing antennas for supply‐chain and particularly for navigation media system which is the case‐study. Further the parametric study and final dimensions of the design and the simulation results are discussed. The proposed design is fabricated and the measurements of the radiation pattern and the return loss are performed proving that the antenna with maximum gain up to 10 dBi and S 11 up to −30 dB, exhibits excellent performance for all the frequencies required in the navigation media systems such as 1.6, 1.8, 2.3, 2.4, 2.6, 3.6, and 5.8 GHz. The proposed design was implemented and tested inside a tracking device mounted on a vehicle and compared with existing commercial antennas. This study showed that the proposed antenna is suitable for tracking devices as it is miniaturized for internal integration and it has better 4G and GPS signal detection and low power consumption comparatively with existing commercial antennas.